2006
DOI: 10.2298/vsp0606545v
|View full text |Cite
|
Sign up to set email alerts
|

Relation between both oxidative and metabolic-osmotic cell damages and initial injury severity in bombing casualties

Abstract: The initial oxidative damages of the cellular membrane with intracellular metabolic disorders contributed to the gradual development of metabolic-osmotic damages of cells, which, consequently caused the OG increase. In the bombing casualties, oxidative cell damages were dependent on the initial injury severity, while metabolic-osmotic cell damages were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The generated free radicals, such as hydrogen peroxide, superoxides, nitric oxide (NO), etc., also cause excitotoxicity and impair the metabolic activity of cells. Further, superoxide radicals generated due to catalytic activity after TBI react with NO to form another potent oxidant peroxynitrite, which impairs cerebrovascular function [ 105 , 106 ]. The ROS possesses an unpaired electron and thus, readily binds to different macromolecules such as protein, nucleic acid, or lipid to cause damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The generated free radicals, such as hydrogen peroxide, superoxides, nitric oxide (NO), etc., also cause excitotoxicity and impair the metabolic activity of cells. Further, superoxide radicals generated due to catalytic activity after TBI react with NO to form another potent oxidant peroxynitrite, which impairs cerebrovascular function [ 105 , 106 ]. The ROS possesses an unpaired electron and thus, readily binds to different macromolecules such as protein, nucleic acid, or lipid to cause damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…This mechanism is fundamental due to the fact that the brain is highly susceptible to free radical damage because of its oxidative metabolism and its high levels of polyunsaturated lipids [42]. Some studies have demonstrated that superoxide radicals and nitric oxide impair cerebral vascular function after TBI due to their strong oxidative effects [43, 44]. …”
Section: Cellular and Molecular Alterations After Tbimentioning
confidence: 99%
“…Due to the biochemical nature of BOP compared to physical nature of TBI (impact or penetrating injury), subtle molecular changes such as free radical-mediated oxidative stress occur and contribute to the manifestation of BOP-induced brain injury ( 40 , 44 , 110 ). Previous studies have demonstrated that reactive oxygen species such as the superoxide radicals and nitric oxide can form peroxynitrite, a powerful oxidant that impairs cerebral vascular function following blast-induced brain injury ( 46 , 111 ). Cernak et al reported that bilateral vagotomy successfully mitigated bradycardia, hypotension, and apnea caused by blast; prevented extreme metabolic alterations and brain edema; but failed to eliminate oxidative stress in the brain due to blast ( 48 ).…”
Section: Blast Brain Injury and Oxidative Stressmentioning
confidence: 99%